Academic Career In Malaysian Higher Education: The Identities Of Malaysian Professors - Safiah , Sidek; Shahrulanuar , Mohamed; Norliah, Kudus; Mahadi, Abu Hassan; Sazelin, Arif; Noor Azlin, Bidin; Mohd Taib, Dora; Mohd Fadzil , Mohd Idris (2013)
This paper describes the identities of Malaysia professors contextualized within the agenda of Malaysia higher education to become the hub higher education in the Asian Pacific region by 2020. in response to the challenges of global higher education, the Malaysian higher education has introduced a systematic strategic plan to develop a culture of academic excellence. However, little has been written about the changes in the academic career in response to this agenda. Future , there are claims that the academic's responsibilities are becoming more diversified and complex as the landscape of higher education changes is emphasis to massification, internationalization and accountability. Draw from this context, this paper aims to explore the roles of academics, particularly the professors and critical analysis of the Malaysian Higher Education policy documents, this paper describes a profile of Malaysian Professors. It also puts forth an argument that the identities of Malaysian professors are characterized by the local and global imperatives as they are shaped by not only the specific agenda of the country but also the global trend. Thus, this paper serves as awareness and guidance for young academics pursuing for professorship to strategize their career pathway in higher education sector.